ЭТНОНИМЫ В ТОПОНИМИИ КАРАКАЛПАКСТАНА - Алланиязов, А. (SCIENCE and SOCIETY, 2022)
The article studies the toponyms of Karakalpakstan formed from ethnonyms. The ethnotoponyms of Karakalpakstan, as shown by their special study, can be divided into the following groups: 1) toponyms formed from the names of the Karakalpak tribes and clans; 2) toponyms derived from the names of Kazakhsikhs, Uzbeks and Turkmens; 3) toponyms formed from the names of peoples.
Keywords: linguistics; onomastics; ethnonym; toponym; ethnotoponym